Biopharmaceutical aspects of technology of woundhealing gels containing silver(I) complex with 2-(4,6-di-tert-butyl-2,3-dihydroxyphenylsulphanyl)acetic acid - Harbatsevich, Hleb I.; Stakhevich, Sergei I.; Loginova, Natalia V.; Ksendzova, Galina A.; Osipovich, Nikolai P.; Slabko, Irina N.; Butkevich, Vasily V.; Makarevich, Zhanna A.; But’ko, Lyudmila V. (Journal of the Belarusian State University. Chemistry, 2019)
The object of the work is to develop optimal composition of a gel with woundhealing ability based on Ag(I) complex with 2(4,6ditertbutyl2,3dihydroxyphenylsulphanyl)acetic acid to produce a novel effective remedy. It was found that propylene glycol (PG) favours the formation of more fine suspension of Ag(I) complex, and introduction of polyvinylpyrrolidone (PVP) hinders aggregation of the particles of the complex, thus providing optimal dispersity of the gel suspension. The gels based on methyl cellulose (MC) are characterized by an acceptable degree of release of Ag(I) complex. It is the gels containing PG and PVP that are characterized by the most complete release of the active substance, which is in agreement with the data on the optimal dispersity. It was found that PG and PVP being introduced into the gel composition increase the osmotic activity of the gel considerably. The optimal composition of the ointment base was determined, %: MC – 3.5; PVP – 5.0; 0.1 mol/L citric acid solution – 5.0; PG – 20.0; water for injections – up to 100.0. The gel obtained was shown to surpass «Dermazin» cream and «Levomecol» ointment in woundhealing ability, while the content of the active substance was significantly lower (0.5 %), and to promote wounds to be cleansed of microorganisms fast and completely too. No accumulation of silver in the liver was found when the gel was used medicinally.
Keywords: silver(I) complex; hydrogel; methyl cellulose; rheological properties; release of the active ingredient; wound-healing ability